Outcomes of burn patients presenting with hypotension within 48 hrs of admission to a level 1 Burn Centre - C.M. Burns; K.D. Boffard; M.S. Moeng (Elsevier, 2024)
Introduction: Burns is one of the important presentations in trauma surgery in both first and third-world countries. Hypotension is often seen in the clinical presentation of a burn injury. Hypotension is the strongest independent predictor of an adverse outcome, according to a study done on emergency departments' hospital outcomes; the lower the systolic, the worse the outcome. No direct study shows that presenting with or developing hypotension within 48hrs of admission and burn injury will have a worse outcome in our low-middle income setting. Objectives: To determine the outcomes of burn patients who developed hypotension within 48hrs of arrival at a Burn Centre in Johannesburg. In a singled time event. Methods: A retrospective descriptive study was conducted at a Level 1 Trauma Centre Burn unit in Johannesburg from 01 Jan 2019 to 31 Dec 2020. Patients who had a hypotensive episode at any point during the 48 h period were recruited. Hypotension was defined as a systolic blood pressure of less than 90mmhg. The patients were then divided into two groups: those who presented with or developed hypotension within 48hrs and those who did not. After that, the in-hospital mortality of both groups was to be determined. The study included all the patients who presented to the Burn Centre. Those younger than 18, or requiring readmission in the same study or delayed admissions of more than 24 h were excluded. Demographics, burn information, resuscitation data, outcomes and disposition status were evaluated. The STATA Statistics/Data Analysis version 16.0 was used to analyse the data. The level of significance was set at a p-value < 0.05. Ethical approval was obtained from the Human Research Ethics Committee (HREC) (medical) of the University of the Witwatersrand with the clearance number: M220132. Results: Of the 132 patients seen, only 105 met the study inclusion criteria. Most patients were male: 91/105 (86.6 %). Flame burns accounted for the majority of the burns, 64/105 (60.95 %), followed by electrical burns, 26/105 (24.76 %). Hot water and chemical burns only accounted for 11/105 (10.48 %) and 4 (3.81 %) cases. Hypotension within 48hrs was noted in 37/105(35 %) of the cases. Hypotensive patients had an increased burn depth (p = 0.03), higher inhalation rate component (p = <0.001), greater lactate levels(p = 0.00001), higher baux score(p = 0.00001) and more likelihood of being placed on the ventilator (p = <0.00001) or dialysis (p = 0.008). Mortality was noted in 16 (43 %) of the patients who developed hypotension compared to 5 (7.4 %) patients of non-hypotensive patients (p < 0.001). The mortality of patients who presented with or developed hypotension was 9.59 times (95 % CI 3.1-29.4; p = 0.00001) higher than those who did not develop hypotension. Age and TBSA affected by burn, were found to have significant predictive value for mortality (p < 0.0001), respectively. Propensity matching was limited due to sample size. TBSA and the development of hypotension were matched, and the odds ratio of developing mortality was still increased. Conclusion: Hypotension was seen among burn injury patients admitted to a specialized intensive care unit. Hypotension was associated with higher TBSA % and increased age. In terms of characteristics, increased used of organ support was more likely with hypotensive patients with ventilation, inotropes, and dialysis. Length of stay was decreased in hypotensive patients. The odds of mortality were much higher in hypotensive patients, with age and TBSA being significant variables.